Implementing elliptic curve cryptography on communication key in elliptic curve integrated encryption scheme / Muhammad Haziq Mohd Jefry, Mumtazatun Nisa’ Aidil Fizza and Naf’an Nasha - Mohd Jefry, Muhammad Haziq; Aidil Fizza, Mumtazatun Nisa’; Nasha, Naf’an (2022)
In today’s modern world, most data transactions and communications are made through online channel. However, exchanging data over an insecure channel is harmful since malicious actors would use the data to their benefits. Therefore, to ensure the security when making data transmission online, cryptography was introduced. Security and efficiency of cryptosystem depends on the mathematical problem that it is based on. Despite that, when a cryptosystem has been created for quite a long time, the cryptosystem might have been broken by hacker. Hence, it is important for cryptographer to develop a more secure and advanced cryptosystem. In this project, we will be examining the current state of knowledge about Diffie-Hellman Key Exchange (DHKE) protocol and Elliptic Curve Diffie-Hellman (ECDH), modifying communication keys from numbers to point based on Elliptic Curve Cryptography (ECC) and changing the method of establishment of communication keys from multiplication law to addition law. With the new method that we have proposed, we hope that it can benefit academicians for future research and can be implemented in real world.